Legal Policy and Challenges in Protecting Sustainable Food Agricultural Land in Indonesia: A Constitutional and Criminal Law Perspective - Emha, Zidney Ilma Fazaada; Arifin, Ridwan; Napitupulu, Michael Timothy; Putri, Destashya Wisna Diraya; Putri, Nadiyah Meyliana (The Indonesian Journal of International Clinical Legal Education, 2024)
Indonesia, as a legal state under Article 1(3) of the 1945 Constitution, aspires to achieve sovereignty, justice, and prosperity. Food sovereignty is essential to realizing these constitutional ideals. Law Number 41 of 2009 on the Protection of Sustainable Food Agricultural Land (PLP2B) serves as a key legislative framework to safeguard agricultural land. However, its implementation faces significant challenges, including weak enforcement mechanisms, limited coordination among stakeholders, and insufficient public awareness. These obstacles hinder efforts to prevent land conversion and ensure sustainable food security. This research addresses the urgency of fulfilling the constitutional mandate outlined in the second and fourth paragraphs of the Constitution’s Preamble, emphasizing sustainable development and societal welfare. Through a normative juridical approach, this study analyzes the legal policy for protecting agricultural land from constitutional and criminal law perspectives, offering a novel critique of the existing framework. Findings indicate gaps in regulatory synchronization, the absence of effective criminal sanctions to deter violations, and weak institutional coordination. To address these issues, the study recommends strengthening legal provisions, imposing stricter sanctions for land conversion, and improving inter-agency collaboration to ensure effective land protection. This research contributes to the development of legal science by offering practical recommendations for enhancing sustainable land protection policies. It provides valuable insights for policymakers, legal practitioners, and law enforcement agencies, supporting efforts to achieve food sovereignty and improve community welfare in Indonesia.